2021
DOI: 10.1371/journal.pone.0246997
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of inflammatory mediators in brain extracellular fluid in paediatric TBM

Abstract: Tuberculous meningitis (TBM) is the most fatal form of tuberculosis and frequently occurs in children. The inflammatory process initiates secondary brain injury processes that lead to death and disability. Much remains unknown about this cerebral inflammatory process, largely because of the difficulty in studying the brain. To date, studies have typically examined samples from sites distal to the site of disease, such as spinal cerebrospinal fluid (CSF) and blood. In this pilot study, we examined the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several limitations to existing data, and future challenges in TBM research exist. In a small brain microdialysis study in paediatric TBM, brain extracellular fluid (ECF) cytokine levels were lower than ventricular CSF, which were in turn lower than lumbar CSF ( 133 ). In addition, Rohlwink et al.…”
Section: Discussionmentioning
confidence: 98%
“…Several limitations to existing data, and future challenges in TBM research exist. In a small brain microdialysis study in paediatric TBM, brain extracellular fluid (ECF) cytokine levels were lower than ventricular CSF, which were in turn lower than lumbar CSF ( 133 ). In addition, Rohlwink et al.…”
Section: Discussionmentioning
confidence: 98%
“…However, levels of cytokines in the tissues and organs can be highly variable. A cytokine panel used in patients with tuberculous meningitis indicated that all (except IL-10) were present in brain at levels lower than in CSF ( Loxton et al, 2021 ), while a panel of 36 cytokines used by Lepennetier et al (2019) exhibited little correlation between serum and CSF levels in a variety of neurological disorders. Similarly, measurements of TNF, IFN-γ, IL-6, IL-8, and IL-10 revealed no correlation between plasma and CSF levels ( Ellison et al, 2005 ), and a meta-analysis of patients with MDD found no relationships between IL-6 or TNF levels in blood and CSF or with PET-scan markers of inflammation ( Enache et al, 2019 ).…”
Section: Limitations and Uncertainties: Concentrations And Correlationsmentioning
confidence: 99%